Origin of a rapidly evolving homeostatic control system programming testis function. Issue 2 (August 2017) - Bu, Pengli; Yagi, Shintaro; Shiota, Kunio; Alam, S M Khorshed; Vivian, Jay L; Wolfe, Michael W; Rumi, M A Karim; Chakraborty, Damayanti; Kubota, Kaiyu; Dhakal, Pramod; Soares, Michael J
Abstract : Mammals share common strategies for regulating reproduction, including a conserved hypothalamic–pituitary–gonadal axis; yet, individual species exhibit differences in reproductive performance. In this report, we describe the discovery of a species-restricted homeostatic control system programming testis growth and function. Prl3c1 is a member of the prolactin gene family and its protein product (PLP-J) was discovered as a uterine cytokine contributing to the establishment of pregnancy. We utilized mouse mutagenesis of Prl3c1 and revealed its involvement in the regulation of the male reproductive axis. The Prl3c1 -null male reproductive phenotype was characterized by testiculomegaly and hyperandrogenism. The larger testes in the Prl3c1 -null mice were associated with an expansion of the Leydig cell compartment. Prl3c1 locus is a template for two transcripts ( Prl3c1 -v1 and Prl3c1-v2 ) expressed in a tissue-specific pattern. Prl3c1-v1 is expressed in uterine decidua, while Prl3c1-v2 is expressed in Leydig cells of the testis. 5′RACE, chromatin immunoprecipitation and DNA methylation analyses were used to define cell-specific promoter usage and alternative transcript expression. We examined the Prl3c1 locus in five murid rodents and showed that the testicular transcript and encoded protein are the result of a recent retrotransposition event at the Mus musculus Prl3c1 locus. Prl3c1-v1 encodes PLP-J V1 and Prl3c1-v2 encodes PLP-J V2. Each protein exhibits distinct intracellular targeting and actions. PLP-J V2 possesses Leydig cell-static actions consistent with the Prl3c1 -null testicular phenotype. Analysis of the biology of the Prl3c1 gene has provided insight into a previously unappreciated homeostatic setpoint control system programming testicular growth and function.